PROTECTIVE EFFECT OF COMMIPHORA MUKUL GUM RESIN ON BRAIN IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - G., Sudhakara; B., Ramesh; P., Mallaiah; B., Manjunatha; Saralakumari, Desireddy (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The present study was undertaken to investigate the hypolipidemic activity of ethanolic extract of Commiphora mukul gum resin (EtCMGR) on the brain of streptozotocin (STZ) induced diabetic Wistar rats. Methods: Thirty two rats, included for the study, were divided into four groups: control (C), control treated with EtCMGR (C+CM), diabetic (D) and diabetic treated with EtCMGR (D+CM). Diabetes was induced by single intraperitonial injection of STZ (55 mg/kg b.w.). Results: Diabetic rats showed significant reduction in the levels of total lipids, phospholipids, cholesterol, glycolipids and protein level and significant decrease in the activity of acetylcholinesterase while the levels of triglycerides, acetylcholine and the activities of glutamate pyruvate transaminases (GPT) and glutamate oxaloacetate transaminases (GOT) increased significantly when compared to control group. Oral administration of EtCMGR (suspended in 5% Tween-80 in distilled water prior to use) daily at a concentration of 200 mg/kg b.w. to group-D+CM rats for 60 days reversed the above changes significantly. Conclusion: These results suggest that EtCMGR exhibits hypolipidemic effect in the STZ-induced diabetic rats. Â